Konsep Desain Bangunan Mixed Use pada Plaza Utama Kawasan Al Amin Living Lab & Industrial Park - Dara Wisdianti; Peranita Sagala; Ramayana Ramayana; Ivan Noor Akbar (Politeknik Kampar, 2024)
Al Amin Living Lab and Industrial Park is an area located in Sampe Cita Village, Kutalimbaru District. The area is designed as a center for learning activities, practicum, research, service and innovation center of Universitas Pembangunan Panca Budi. To support all these activities, various supporting facilities are also designed, one of which is a mixed use building that will be placed in the main plaza of the area which is planned to be the center of activity for the entire area. The Mixed Use building is a combination of buildings with different functions, a combination of residential, commercial, and cultural buildings that are planned. The research will describe the concepts used in designing Mixed Use buildings in the main plaza of the area, which can support all activities planned in the Al Amin Living Lab and Industrial Park area.